Implementing the Balanced Scorecard in Excel for small and medium enterprises - Vieira, António Amaro Costa (2017)
Performance measurement is a way for organizations to be able to assess processes' performance. The Balanced Scorecard (BSC) is one of the best-known performance measurement systems. However, many small and medium enterprises (SME) face problems when trying to implement these frameworks, due to software associated costs. In this context, this paper documents the work conducted to develop a low cost solution for SME. The solution consisted on implementing the BSC in an excel workbook. The created tool allows users to have a chromatic view over data and assess its quality, by introducing risk analysis, through the utilization of trails with different intensities, depending on the associated risk. Moreover, data is automatically recorded to allow traceability and dynamic charts were introduced to allow the analysis of different performance attributes.